Exploring traditional games in a literature review: How they affect the physical fitness of junior high school students - Fufu, Ronald Dwi Ardian; Yuliana, Yuliana; Tajuddin, Al Ihzan; Wijaya, I Nyoman Wahyu Esa; Neolaka, Erwin Sarnoto (Universitas Tanjungpura, 2026)
Background. One of the most important factors enabling students to participate effectively in physical and artistic activities is physical fitness. In addition, practical activities can positively influence students' work habits in the cognitive, affective, and psychomotor domains. Objectives. The purpose of this study is to analyze the physical fitness profile of junior high school students in Indonesia and to identify factors that influence students' physical fitness levels. Methods. This study uses the PRISMA guidelines. Literature searches were conducted using several sources, including Google Scholar, books, Web of Science, and other relevant databases. The search process was carried out using the keywords physical fitness, junior high school students, and physical education. A total of 199 publications were identified through database searches (Google Scholar, PubMed, and ScienceDirect). After applying the inclusion and exclusion criteria, only nine articles met the eligibility requirements and were included in the final analysis. Results. The overall findings indicate that the physical fitness of junior high school students in Indonesia still faces significant challenges. Most students fall into the low to moderate physical fitness category, while only a small proportion achieve a good fitness level. Several studies show that creative learning interventions, such as traditional games, can effectively improve students’ physical fitness. In addition, environmental factors and physical activity outside of school also play an important role, although their effects may vary. Conclusion. Based on findings from reviewed journals, the level of physical fitness among junior high school students is still relatively low. This condition is indicated by the limited time allocated for physical education classes and the lack of regular sports activities among students. Therefore, the integration of traditional games into physical education at the junior high school level is important as an effort to improve students' physical fitness while preserving the nation's cultural heritage.